ABUNDANCE AND DISTRIBUTION PATTERN OF MANGROVE SNAIL Telescopium telescopium IN THE DARUL AMAN COASTAL OF RUPAT, BENGKALIS DISTRICT, RIAU - Andita, Hardianto; Mulyadi, Aras; ', Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted on September to October 2014. The study aims were to determine the abundance, size distribution and distribution pattern of mangrove snail (T. telescopium) in the Darul Aman Coastal Bengkalis Regency. The method used was a survey method. Samples of snail population and sediment were collected by a single visit during low tide. Location of study was divided into 3 stations. Station I have grow rare mangrove, residential community and coastal abrasion, station II have dense and closely mangrove, station III have close with river estuary, rarely struck high tide because higher dan mangrove grow rarely than. The sample analysis carried out in Marine Biologi Laboratory of Fishery and Marine Science Faculty of Riau University.The results of the study show that the highest abundance of snail was at the station III (2,05 ind/m2) and the lowest was at the station I (0,6 ind/m2). The most dominant of size distribution is 81 – 90 mm. Distribution pattern in this area is uniform with Id between 0,88 – 0,98.Keywords: Telescopium telescopium. abundance. distribution. Darul Aman coastal